MORPHOLOGICAL CHARACTERISTIC OF FATAL CASES AFTER SPLENECTOMY UNDER EXPERIMENT - V. M. Timerbulatov; R. R. Fayazov; B. F. Chanyshev; F. A. Kayumov; Sh. V. Timerbulatov (Креативная хирургия и онкология)
Experimental  investigation showed that  through short-term after splenectomy the death rate  of  white  rats  was  16,25%.  Morphological investigation indicates  that  animals have  postinfectious  hepatitis  and   the   first  stage of  pulmonary  tissue   inflammation. Mesenteric lymphatic nodes  as the organs of hemoand immune  cytopoiesis  appear to be under  condition of pronounced functional tension in response to inflammation.